Análisis de los mecanismos de transición de IPV4 a IPV6 e implementación de una solución para la red del proveedor de servicios de internet DEUSSOFT & Telecomunicaciones de la ciudad de Santa Rosa - Pesántez Ochoa, Diego Eduardo (2014)
The company DEUSSOFT & TELECOM of Gold City of Santa Rosa, provides Internet services, hosting and development of computer systems, this means using Information Technology to offer products and solutions in innovative ways; but the company did not have the IPv6 service.